PERBANDINGAN KECEPATAN RATA â€“ RATA KENDARAAN DENGAN KECEPATAN ARUS BEBAS ( KAJIAN WILAYAH STUDI: JALAN ARTERI SLAMET RIYADI - SAMARINDA ) - ADE, LA (KURVA S JURNAL MAHASISWA, 2014)
Arterial roads Slamet Riyadi - Samarinda is one of the roads that have the characteristics of road users undisipline . One form of indiscipline that is driving the vehicle at high speed while on the road , so the traffic accidents often occur on these roads . This scientific article aims to evaluate the ratio between the average speed of vehicles in free flow speed . Analysis of the average speed of vehicles using the comparative approach between distance and time , and the results obtained 47.94 km / h , free flow speed analysis using the formula FV = ( FVO + FVW ) x FFVSF x FFVCS and the results obtained 47.97 km / h . The analysis showed that the speed of the motorcycle is at its highest proportion among the other vehicle speed , the amount of 70.37 km / h , with the difference in the speed of MKJI 1997 ( 40.42 km / h ) at 10.21 Â km / jam.Perbandingan results of the analysis showed that the velocity average - average > free flow speed to the increment speed of 1.78 km / h , so that the necessary repairs around traffic management to reduce road accidents .